2017
DOI: 10.1364/ol.42.000290
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution distributed optical fiber dynamic strain sensor with enhanced frequency and strain resolution

Abstract: A distributed optical fiber dynamic strain sensor with high spatial and frequency resolution is demonstrated. The sensor, which uses the ϕ-OTDR interrogation technique, exhibited a higher sensitivity thanks to an improved optical arrangement and a new signal processing procedure. The proposed sensing system is capable of fully quantifying multiple dynamic perturbations along a 5 km long sensing fiber with a frequency and spatial resolution of 5 Hz and 50 cm, respectively. The strain resolution of the sensor wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 8 publications
1
62
0
1
Order By: Relevance
“…However, a more precise quantitative measurement of an external disturbance requires additional information on the change in signal behavior induced by strain or temperature changes. To this end, techniques which are based on frequency shift measurements [36][37][38][39] and others using direct demodulation of the phase change [35,[40][41][42][43][44] have been proposed. The frequency shift method for external impact extraction using ϕ-OTDR is based on the observation that the frequency of the probing pulses can be matched with a corresponding change in temperature or strain with some proportionality constant.…”
Section: ϕ-Otdr Sensors For Precise Impact Extraction Using Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…However, a more precise quantitative measurement of an external disturbance requires additional information on the change in signal behavior induced by strain or temperature changes. To this end, techniques which are based on frequency shift measurements [36][37][38][39] and others using direct demodulation of the phase change [35,[40][41][42][43][44] have been proposed. The frequency shift method for external impact extraction using ϕ-OTDR is based on the observation that the frequency of the probing pulses can be matched with a corresponding change in temperature or strain with some proportionality constant.…”
Section: ϕ-Otdr Sensors For Precise Impact Extraction Using Frequencymentioning
confidence: 99%
“…The technique is used to demonstrate dynamic measurement of strain varying at 5 kHz over a 1 km distance with a minimum detectable strain range of 80 nε [40]. This scheme has recently been improved in terms of the performance in both the spatial and frequency resolutions [41]. The later configuration involves the use of a single FBG to filter the ASE noise both in the propagating pulses and the backscattering signal.…”
Section: ϕ-Otdr Sensors For Precise Impact Extraction Using Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Fang et al (Fang 2015) demonstrated an alternative implementation of this technique using an imbalanced Michelson interferometer instead of MZI. More recently, Masoudi and Newson (Masoudi 2017) have proposed a modified the experimental setup and signal processing procedure to improve the sensitivity and spatial resolution of the DVS to 40nε and 50cm, respectively.…”
Section: B) Interferometry Techniquementioning
confidence: 99%
“…Luckily, significant progress has been made in developing distributed optical fiber sensing (DOFS) systems, making them a promising approach for the vibration-sensitive measurement of transportation, due to their fully distributed nature [5][6][7]. The DOFS can locate the external dynamic disturbances at any position of optical fiber with meter-scale spatial resolution over tens of kilometers [8]. Importantly, long distance coverage can be economically achieved with optical fiber as the equivalent sensing arrays.Generally, the DOFS can be divided into Brillouin-based DOFS and Rayleigh-based DOFS in terms of vibration detection.…”
mentioning
confidence: 99%